Perceptions of Yemeni physicians about sources of drug information and factors predicting their choices - Mahmoud Al-Areefi, Mohamed Izham Mohamed Ibrahim, Mohamed Azmi Hassali, Abubakr Alfadl (Journal of Applied Pharmaceutical Science, 2021)
High-quality information is a necessary prerequisite for an optimum prescribing decision that enhances patient healthcare outcomes. Therefore, the purpose of this study was to identify the main sources of information used by physicians to obtain knowledge about new drugs and to identify the relationship of physicians’ characteristics and practice-setting factors with their choices of sources of drug information. To achieve this objective, a cross-sectional study was conducted through a questionnaire distributed among physicians in the public and private sectors. Descriptive analysis, factor analysis, t-tests, and analysis of variance were carried out to test the differences in the score of “sources of drug information” between categories of physicians’ characteristics and practice-setting factors. The study revealed that the majority (96.2%) of physicians considered medical representatives (MRs) to be their primary source of information about new drugs. Also, MRs seen per week were shown to exert significant differences between groups of physicians for all types of drug information sources, with the exception of noncompany information. In addition, significant differences were seen between groups of physicians sorted by academic affiliation for all types of drug information sources. In conclusion, the majority of physicians use MRs as the main source of information about new drugs. Also, among physicians’ characteristics and practice-setting factors, academic affiliation was one of the most influential factors in identifying physicians’ preference for sources of information about new drugs.
Keywords: Physicians, medical representatives, sources of drug information, Yemen